Tipologi, Tahapan Inovasi Dalam Pelayanan Publik: Pendekatan Fokus Dan Lokus Dalam Analisis Faktor Kunci Keberhasilan - Mozin, Sri Yulianty; Ma’ruf, Riskawati; Kadir, Fitra (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Innovation in public services is an urgent necessity for modern bureaucracy to respond to societal dynamics, technological shifts, and demands for transparency. This article examines the typology and stages of public service innovation through the lenses of